Modelling the strain rate sensitivity on the subsurface damages of scratched glass ceramics. Issue 15 (15th October 2017) - Yang, Xue; Qiu, Zhongjun; Lu, Cui; Li, Xue; Tang, Junjie
Abstract: Some applications of glass ceramics components require high surface finish and low subsurface damage. However, the machining process of glass ceramics can easily cause surface and subsurface damage. To reveal the dynamic effect of strain rate caused by machining speed on damage induced during machining, this paper proposes a new theoretical stress field model in which the strain rate effect is introduced for estimating plastic deformation and cracks. This model was established based on the relationship between the strain rate and material properties. This model provides an insight into the effect of strain rate and scratch speed on plastic deformation and cracks. To validate the present model, scratch experiments were conducted on glass ceramics using an ultra-precision machine. The findings show that the plastic deformation radius, and median crack length decrease as scratch speed increases, while the actual ductile-to-brittle transition depth increases with the increase of the scratch speed. Furthermore, the area of the plastic zone and median crack length as predicted by the developed model were compared with experimentally obtained values. The comparison results show that the predicted values are consistent with the experimental measurements. Thus, the proposed model can evaluate the plastic deformation and median crack length, which determine the dimension of the subsurface damage layer. This study is expected to provide guidance for machining-induced damage design and the manufacture and application of glass ceramic components.